Rediscovering the mosquito fauna (Diptera: Culicidae) of Estonia: an annotated checklist with distribution maps and DNA evidence - Kirik, Heli; Tummeleht, Lea; Kurina, Olavi (Zootaxa, 2022)
Female mosquitoes (Diptera: Culicidae) affect their hosts in numerous negative ways and are crucial to the spread of vector-borne pathogens. It is, therefore, important to have a detailed overview of regional mosquitoes, to be able to detect changes in species diversity and identify possible health threats. The aim of this study was to update the checklist of the mosquito fauna of Estonia for the first time since 1957. For this purpose, 24,344 adult mosquitoes (94% females) were collected in Estonia from 2008 to 2020 using various trapping methods. Specimens were primarily identified by morphological characteristics, but DNA barcoding based on the partial cytochrome c oxidase subunit 1 gene (COI) was also used. Species were included in the checklist based on historical records as well as new collections, while also considering reports from neighboring countries. Species records are supplemented with voucher specimens, distribution maps and DNA evidence. The updated checklist includes 34 species, 27 of which were confirmed with recently collected material. All in all, Aedes communis (de Geer, 1776) proved to be the most common mosquito in Estonia, accounting for 30.1% of the specimens collected. This is noteworthy, as this species has been implicated in the transmission of multiple disease agents present in the area. New evidence revealed the presence of Ae. hexodontus Dyar, 1916, Ae. sticticus (Meigen, 1838), Anopheles messeae Falleroni, 1926 and Culiseta bergrothi (Edwards, 1921) in Estonia.